Effects of Rainfall Variability on Farm Income Disparity and Inequity in a Small Catchment of Northern-Thailand: a Multi-Agent Simulation Investigation - Nicolas Bécu (Territoire en Mouvement)
This paper presents a modeling approach, based on multi-agent-systems, for assessing the effects of inter-annual rainfall variability on income disparity among farms sharing water resource. The study case is a catchment of northern-Thailand where two villages share water for irrigation. Input data were collected and the model was calibrated for this study case and the results described here originate from the simulations undertook. They show that stress events such as dry years tend to increase economic disparities among farms (gross margins and farm income), both at the village scale and between the two villages sharing water. Additional analyses indicate that land-use change which increase irrigation demand, tend to increase farm inequity as well. As so, in contexts of limited resources and due to heterogeneity of resource access and means, inequity among user groups would be positively correlated to the pressure on the resource. Consequently and in the context of climate change, this paper advocates for a wider use of economic assessment tools capable of taking into account spatial and temporal heterogeneity of resource access, such as multi-agent simulations, in order to monitor and anticipate effects on inequity.